1999
DOI: 10.1046/j.1440-1673.1999.433667.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in breast tangent radiotherapy: A survey of practice in New South Wales and the Australian Capital Territory

Abstract: The breast is a complex anatomical structure where achieving a homogeneous dose distribution with radiation treatment is difficult. Despite obvious similarities in the approach to such treatment (using tangents) there is variation in the process of simulation, planning and treatment between radiation oncologists. Previous Australasian studies in the treatment of lung cancer, prostate cancer and Hodgkin's disease highlighted considerable variation in many areas of treatment. As part of a multicentre breast phan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Only 6.3% of patients received CT-planned radiotherapy. This is similar to an old Australian survey that reported that only 3 out of 11 Australian institutions used CT treatment planning [30]. The two centres in Nigeria practising CT treatment planning were able to view the geometry of the target volumes, organs at risk, determine the central lung dose (which did not exceed 2cm), and set up patients and beams to receive homogenous doses.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Only 6.3% of patients received CT-planned radiotherapy. This is similar to an old Australian survey that reported that only 3 out of 11 Australian institutions used CT treatment planning [30]. The two centres in Nigeria practising CT treatment planning were able to view the geometry of the target volumes, organs at risk, determine the central lung dose (which did not exceed 2cm), and set up patients and beams to receive homogenous doses.…”
Section: Discussionsupporting
confidence: 80%
“…The two centres in Nigeria practising CT treatment planning were able to view the geometry of the target volumes, organs at risk, determine the central lung dose (which did not exceed 2cm), and set up patients and beams to receive homogenous doses. The benefits of CT treatment planning have been reported to include better dose precision, dose homogeneity and patient positioning [30]. The ability to conduct 3-dimensional dose calculations and view the geometric positions of the tumor and healthy tissue on a treatment plan are significant advantages that enable the calculation and optimisation of dose [31].…”
Section: Discussionmentioning
confidence: 99%
“…The use of CT has increased rapidly in the last years and all centers now routinely use CT scans for treatment planning. A survey in the United Kingdom, performed between 1997 and 1999, showed that only 2 out of 46 institutions used CT. 12 Australian surveys published in 1999, reported that 3 out of 11 institutions used CT 13 and in 2001 the numbers increased to 10 out of 20 institutions. 8 Another survey reporting on the period 1998-2002 showed that 66 out of 102 radiation oncology practices in Australia and New Zealand used CT-based treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…A number of surveys of practice for the delivery of breast radiotherapy have been produced, 5,7,11,12,[14][15][16] although this is the first such study reflecting Australasian practice. Variations in practice will probably always exist and there are many reasons why this may be so.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of Patterns of Care studies (PCS) or surveys of radiotherapy treatment for different malignancies have been performed and reported in the literature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Many of these have led to improvement in practice by helping to formulate guideline recommendations with resultant improvement in patient outcome.…”
Section: Introductionmentioning
confidence: 99%